2020
DOI: 10.1159/000508824
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Method Study on Strategies in Everyday Personal Goals among Community-Dwelling Older Adults

Abstract: Introduction: Although it is well known that preference for selection, optimization, and compensation (SOC) strategies is associated with indicators of successful aging and wellbeing, very little is known about what predicts the use of SOC as goal management strategies in the daily lives of older adults. The present study investigates predictors of self-reported use of SOC strategies in community-dwelling adults. We expected selection and especially compensation to be higher in individuals with worse subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Even though the aging workforce impacted the organizational bottom line, this effect of using SOC strategies was mediated through the resources of physical and mental functions. Similar results [15,45] were found, where using SOC strategies might be more capable of adapting to change the age-related resource loss and maintain resources to reach required performance and well-being. Furthermore, by examining the effects of SOC strategies in individual, family, work, and society, this study also supported the implications of the SOC literature and aging research.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Even though the aging workforce impacted the organizational bottom line, this effect of using SOC strategies was mediated through the resources of physical and mental functions. Similar results [15,45] were found, where using SOC strategies might be more capable of adapting to change the age-related resource loss and maintain resources to reach required performance and well-being. Furthermore, by examining the effects of SOC strategies in individual, family, work, and society, this study also supported the implications of the SOC literature and aging research.…”
Section: Discussionsupporting
confidence: 76%
“…Using SOC is one of the resources and also a coping strategy for individuals. SOC strategies are related to health resources and well-being [19,45]. A review by Hobfoll et al [19] indicated that similar to COR theory, SOC theory "focused on gain and loss of resources and the inevitable loss of resources that accompanies aging-which, in turn, demands a realignment of available resources to compensate for failing ones" [46].…”
Section: Soc Strategies As Mediator Between Health Resources and Well-beingmentioning
confidence: 99%
“…In that respect, comparing objective cognitive performance with self-reported goals in a mixed method design (i.e., using both qualitative and quantitative data sources and analyses) could help understanding how maintaining or abandoning daily-life goals is related to cognitive status. For instance, followingup on the present data, and using objectively measured cognitive performance on the same participants, we showed that poorer self-reported health and cognitive performance significantly predicted higher use of compensation strategies as reported in the interviews (Joly-Burra et al, 2020). Mixed-methods using interviews therefore appear as a promising tool for future research to investigate participants' own perception of the buildup, maintenance, and activation of reserves across the lifespan, and particularly in old age.…”
Section: Limitations and Perspectivessupporting
confidence: 54%
“…She invited participants to a relaxed yet structured discussion concerning their goals, encouraging them to give as much context and details as they needed to illustrate their narratives. The interview structure and associated visual material support can be found in Appendix A of the Supplementary Material by Joly-Burra, Van der Linden, and Ghisletta (2020). The interviews lasted between 45 minutes and 2 hours and were fully audio-taped.…”
Section: Semistructured Interviewmentioning
confidence: 99%
“…While the aspects of personal development intrinsic to the individual may still apply in late life, those that are temporally distant and emphasize growth and productivity are less relevant (Carstensen et al, 1999;Fung et al, 2020;Korff & Biemann, 2020). For HBPC veterans, the focus may shift from skill development and achievement to reflecting on past experiences and repurposing existing skills and strengths to face current challenges (Baltes & Baltes, 1990;Carpentieri et al, 2017;Joly-Burra et al, 2020;Remillard et al, 2019). Though not explicitly described in the WH model, cultural factors may drive great variation in what goals in adaptation and coping look like in late life over time.…”
Section: Adaptation and Copingmentioning
confidence: 99%